Efficient and Air‐Stable Aqueous‐Processed Organic Solar Cells and Transistors: Impact of Water Addition on Processability and Thin‐Film Morphologies of Electroactive Materials. Issue 34 (15th October 2018) - Lee, Changyeon; Lee, Hae Rang; Choi, Joonhyeong; Kim, Youngkwon; Nguyen, Thanh Luan; Lee, Wonho; Gautam, Bhoj; Liu, Xiang; Zhang, Kai; Huang, Fei; Oh, Joon Hak; Woo, Han Young; et al.
Abstract: The authors report the development of a desirable aqueous process for ecofriendly fabrication of efficient and stable organic field‐effect transistors (eco‐OFETs) and polymer solar cells (eco‐PSCs). Intriguingly, the addition of a typical antisolvent, water, to ethanol is found to remarkably enhance the solubility of oligoethylene glycol (OEG) side chain‐based electroactive materials (e.g., the highly crystalline conjugated polymer PPDT2FBT‐A and the fullerene monoadduct PC61 BO12 ). A water–ethanol cosolvent with a 1:1 molar ratio provides an increased solubility of PPDT2FBT‐A from 2.3 to 42.9 mg mL −1 and that of PC61 BO12 from 0.3 to 40.5 mg mL −1 . Owing to the improved processability, efficient eco‐OFETs with a hole mobility of 2.0 × 10 −2 cm 2 V −1 s −1 and eco‐PSCs with a power conversion efficiency of 2.05% are successfully fabricated. In addition, the eco‐PSCs fabricated with water–ethanol processing are highly stable under ambient conditions, showing the great potential of this new process for industrial scale application. To better understand the underlying role of water addition, the influence of water addition on the thin‐film morphologies and the performance of the eco‐OFETs and eco‐PSCs are studied. Additionally, it is demonstrated that the application of the aqueous process can be extended to a variety of other OEG‐based material systems. Abstract : A desirable water–ethanol process is developed for ecofriendly and nonhazardous fabrication of polymer electronic devices. The addition of a typical antisolvent, water, to ethanol remarkably improves the solubility of nonionic oligoethylene glycol side chain‐based electroactive materials, which enables the fabrication of efficient and air‐stable organic field‐effect transistors and polymer solar cells.